The therapeutic potential of skin mucus from Asian swamp eel (Monopterus albus): In vivo evaluation and histological evidence - Hilles, Ayah Rebhi; Syed, Mahmood; I. Waly, Mostafa; Kaderi, Mohd Arifin; Ahmed, Qamar Uddin; Hejaz Azmi, Syed Najmul; F. AlAsmari, Abdullah; Ali, Nemat; Alharbi, Metab; Rauf, Mohd Ahmar (Elsevier, 2022)
Objectives The Asian swamp eel (Monopterus albus), is commonly distributed in Asian countries. However, its therapeutic potential has not been thoroughly investigated yet. The current study aimed to evaluate the in-vivo therapeutic properties of the skin mucus of this fish.